Comparative biochemical composition of wild and farm origin grayling (Thymallus thymallus) eggs - Tjaša Kodela; Alenka Levart; Simona Sušnik Bajec (Italian Journal of Animal Science)
In this study, the biochemical composition of wild and farm origin grayling eggs was compared, first, to evaluate the composition of fatty acids and protein content in grayling eggs for the first time, and second, to discover differences in biochemical composition between wild and farm origin eggs which is affected by broodstock feed. Farm origin grayling females were fed commercial trout starter feed, while wild origin females were feeding on food present in their natural environment. Fatty acid composition, protein content and colour were determined. Based on a principle component analysis (PCA) of the biochemical profile, farm and wild origin grayling eggs were clearly separated. Wild origin grayling eggs contained higher amount of SFA, but lower MUFA and PUFA than farm origin eggs. A considerable difference between wild and farm origin grayling eggs was observed also in essential fatty acids: C22:6 n-3 (DHA), C20:5 n-3 (EPA) and C20:4 n-6 (ARA), resulting in higher EPA/ARA and DHA/EPA ratio in farm origin eggs compared to wild origin eggs. Wild origin grayling eggs were characterised by higher protein content and were more intensely red-coloured than farm origin eggs, which were almost colourless. It could be concluded that the biochemical composition of farm origin eggs significantly differs from wild origin grayling eggs, which might have an influence on the embryonic development and hatching success of farm origin grayling. Therefore, the diet that has the greatest effect on egg composition needs to be optimised to meet the needs of the grayling broodstock and to improve the breeding efficiency of farm raised graylings.